Effect on Thermal and Structural Properties of Element Content in CuAlBe Shape Memory Alloys Irradiated with a Constant Gamma Radiation Dose - Balo, Şahide Nevin; Sevin, Abdulvahap (My University, 2023)
Since gamma radiation is a type of radiation that can change the structural properties of materials, CuAlBe shape memory alloy with two different weight percentages was used in this study. CuAlBe shape memory alloys were irradiated with a constant gamma radiation dose of 40 kGy, and the resulting thermal and structural changes in the alloys were investigated. Changes in enthalpy and in the transformation temperature of the alloys were determined by differential scanning calorimetry (DSC), and thermodynamic parameters of alloy samples were calculated. Microstructural changes were determined by X-ray analysis. Microstructural changes were verified by metallographic observations, and microhardness measurements were taken. The study investigated to what extent the physical parameters of CuAlBe shape memory alloys changed depending on the alloying elements when subjected to a constant irradiation dose.
Keywords: Microhardness; gamma radiation; CuAlBe shape memory alloy